In Vitro and in Vivo Antioxidant Effect of the Stem Bark Extract of Pseudocedrela kotschyi in Pentylenetetrazole-kindled Rats. - Abubakar , K.; Danjuma , N. M.; Maiha , B. B.; Anuka, J. A.; Magaji , M. G.; Malami , S. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
This study evaluates the antioxidant and anti-kindling effects of the methanol stem bark extract of Pseudocedrela kotschyi, which is commonly used in folk medicine to treat dysentery, malaria, toothache and rheumatism. To investigate the anticonvulsant activity of the plant, Pentylenetetrazole induced kindling model was employed using fifty rats divided into five groups (n=10). In-vitro antioxidant activity of methanol, n -hexane, chloroform, n-butanol and residual aqueous fractions was evaluated using the DPPH radical scavenging activity method. The total phenolic and total flavonoid contents of the extract and fractions were evaluated. The serum and brain homogenates were investigated for malonyldialdehyde, reduced glutathione, superoxide dismutase and catalase enzyme activity. The extract at doses of100 and 200 mg/kg significantly (p< 0.05 and p< 0.01) protected the rats against PTZ induced kindling (stage 5 convulsion). Lipid peroxidation was significantly inhibited in the brain homogenates at all doses tested (50,100 and 200 mg/kg).Similarly the extract at the test doses increased significantly (p<0.05 –p<0.001) the activities of reduced glutathione, superoxide dismutase and catalase enzyme in both serum and brain homogenates. In conclusion the methanol extract of P. kotschyi stem bark extract may contain bioactive principles with anti-kindling and antioxidant Properties. This may also provide an explanation for its traditional use in the management of epilepsy.